Hardware-software complex for automated control and monitoring of the vacuum system of the coating setup "Bulat-6" - Gubarev, S.P.; Leonovych, A.V.; Muratov, R.M.; Nezovibat'ko, Y.N.; Opaleva, G.P.; Taran, V.S.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2019)
The hardware-software complex for automated control and monitoring of the vacuum system of the coating setup "Bulat-6" is presented. Its use provides the stability of the process of obtaining and maintaining the required vacuum in the plant. The complex is built on the basis of the software-logic controller (PLC) type ELC-22 XLogic. Представлено апаратно-програмний комплекс для автоматизованого управління і моніторингу вакуумної системи установки для нанесення покриттів «Булат-6». Його використання забезпечує стабільність процесу отримання і підтримки необхідного вакууму в установці. Комплекс побудований на базі програмно-логічного контролера (ПЛК) типу ELC-22XLogic. Представлен аппаратно-программный комплекс для автоматизированного управления и мониторинга вакуумной системы установки для нанесения покрытий «Булат-6». Его использование обеспечивает стабильность процесса получения и поддержания требуемого вакуума в установке. Комплекс построен на базе программно-логического контроллера (ПЛК) типа ELC-22 XLogic.